Impact of Janus kinase inhibitors and methotrexate on interstitial lung disease in rheumatoid arthritis patients - Kurushima, Shota; Koga, Tomohiro; Umeda, Masataka; Iwamoto, Naoki; Miyashita, Ritsuko; Tokito, Takatomo; Okuno, Daisuke; Yura, Hirokazu; Ishimoto, Hiroshi; Kido, Takashi; Sakamoto, Noriho; Ueki, Yukitaka; et al. (Frontiers in Immunology, 2024)
ObjectivesLittle is known about how various treatments impact the progression of interstitial lung disease (ILD) in rheumatoid arthritis (RA) patients. Here, we compared ILD progression in RA patients treated with Janus kinase inhibitors (JAKi) or biological disease-modifying anti-rheumatic drugs (bDMARDs). In vitro experiments were also performed to evaluate the potential effects of the drugs on epithelial–mesenchymal transition (EMT), a key event in pulmonary fibrosis.MethodsThis retrospective study included 93 RA-ILD patients who initiated treatment with JAKi, tumour necrosis factor inhibitors (TNFi), or abatacept between 2017 and 2020. Worsening ILD was quantified by changes in chest computed tomography (CT) scans between baseline and follow-up (mean 14 months, range 6–51 months). Response to treatment was evaluated using Disease Activity Score-28 with erythrocyte sedimentation rate (DAS28-ESR). Expression of the EMT marker N-cadherin in A549 lung cells was assessed by western blotting.Results and discussionWorsening ILD was detected in 19.4% (7/36), 16.7% (5/30), and 22.2% (6/27) of patients treated with JAKi, abatacept, and TNFi, respectively. Multivariate analysis identified female gender (P=0.043) and >10% fibrotic lesions (P=0.015) as significant predictors of worsening ILD. DAS28-ESR-based non-responder status was also significantly associated with worsening ILD (P=0.0085). In vitro, combination treatment with methotrexate and baricitinib significantly impeded EMT progression. Worsening ILD was associated with more extensive fibrotic lesions at baseline and female gender in RA patients treated with JAKi or bDMARDs. JAKi and methotrexate co-treatment may prove beneficial in modifying key events underlying the pathogenesis of RA-ILD.